Communication Norm on Digital Network: Interpreting Islamic View on Language Used - Arifin, Ferdi; Hadziq, Abdulloh (The Pontianak State Institute of Islamic Studies, 2021)
Industrial revolution provides social media for communicating and sharing with each other. Yet, this study investigates chosen language on social media comments that is to have many improper and impolite languages based on Islamic views. The method uses in this study utilizing systematic review as a development of the qualitative method, which is classifying and interpreting the obtained data. The finding of this study elaborates language used on social media comments divided into improper and impolite language. The result shows us that improper and impolite chosen language on social media indicate that the users are misunderstanding and ignoring Islamic teaching which is already regulated in the holy Quran. This study concludes that Muslim users might understand Islamic views on the language used on social media.